On the subject of the Ba overabundance in the open clusters stars - Mishenina, T V; Korotin, S A; Carraro, G; Kovtyukh, V V; Yegorova, I A (Journal of physics. Conference series, 2016)
For eight distant open clusters, namely Ruprecht 4, Ruprecht 7, Berkeley 25, Berkeley 73, Berkeley 75, NGC 6192, NGC 6404, and NGC 6583, we determined the yttrium and barium abundances using the UVES, VLT spectra (ESO, Chile). The stars of one young cluster (Ruprecht 7) demonstrate significant barium overabundance(∼0.55 dex) that can not be due to the determination error. We have considered the Ba abundance determination errors due to LTE approach, saturation of the lines, synthetic and observed barium line fitting, and the causes of the Ba overabundance associated with the Galactic disc enrichment or the origin of open clusters. Possible explanation for this overabundance can be the origin of n-capture elements enrichment of the clusters (galactic or extragalactic) or additional sources of the Ba production.